2014
DOI: 10.1111/bju.12652
|View full text |Cite
|
Sign up to set email alerts
|

One‐ vs 4‐week stent placement after laparoscopic and robot‐assisted pyeloplasty: results of a prospective randomised single‐centre study

Abstract: ObjectivesTo determine whether 1-week stenting of the pelvi-ureteric anastomosis of laparoscopic or robot-assisted pyeloplasty is as effective as 4-week stenting, based on their respective success rates. Patients and MethodsA total of 100 patients with pelvi-ureteric junction obstruction were treated by Anderson-Hynes pyeloplasty and the anastomosis was stented using a 6-F JJ catheter for either 1 week (1W series) or 4 weeks (4W series), based on a randomisation protocol. Postoperative follow-up was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…All 17 were observational studies . Thirteen studies had a retrospective design [], three were prospective , and one used both retrospective and prospective data collection . Two studies reported patient matching .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All 17 were observational studies . Thirteen studies had a retrospective design [], three were prospective , and one used both retrospective and prospective data collection . Two studies reported patient matching .…”
Section: Resultsmentioning
confidence: 99%
“…). Ten studies reported similar complication rates between approaches []. Four studies reported complication rates of 0% for both groups .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, laparoscopic pyeloplasty (LPP) has become the standard treatment for PUJ obstruction (PUJO), Open pyeloplasty should only be performed after failed LPP [1]. The success rates of LPP vary between 87% and 100% and are comparable to open pyeloplasty success rates, but with the requisite advantages of being minimally invasive [2].…”
Section: Introductionmentioning
confidence: 99%